MULTIPLE-OBJECTIVE SCHEDULING FOR BATCH PROCESS SYSTEMS USING STOCHASTIC UTILITY EVALUATION - Park, Hongsuk; Shin, Youngchul; Moon, Ilkyeong (International Journal of Industrial Engineering : Theory Applications and Practice, 2024)
Most research studies in the batch process control problem are focused on optimizing system performance. The methods address the problem by minimizing a single criterion, such as cycle time and tardiness, or bi-criteria such as cycle time and tardiness, and earliness and tardiness. We demonstrate the utilization of the Stochastic Utility Evaluation (SUE) function approach to the performance of batch process systems using multiple criteria. Tri-criteria problem is used as an example to illustrate the use of the SUE function. That is, we explore how SUE function with stochastic information can be implemented to improve existing approaches to the batch process control problem. The simulation results demonstrate that strategies based on the SUE function perform better than existing strategies based on static utility values.
Keywords: Batch process control; Batch process systems; Control problems; Earliness; Evaluation function; Mean cycle time; Multiple-objective scheduling; Stochastic utilities; Stochastic utility evaluation function; Tardiness; Batch process system; Earliness; Mean cycle time; Multiple-objective scheduling; Stochastic utility evaluation function; Tardiness